Glass chemical strengthening salt bath additive as well as preparation method and recovery treatment method thereof
By adding salt bath additives composed of SiO2, Na2O, Al2O3, K2O and rare earth oxides to the glass chemically strengthened salt bath, the performance instability caused by the increase of impurity ions during the glass chemically strengthened salt bath is solved, and long-term and stable effective ion concentration maintenance is achieved, and production efficiency and salt bath service life are improved.
Patent Information
- Application Number
- CN202510030181.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
During the chemical strengthening of glass, the increasing number of impurities and ions lead to unstable glass performance. In the prior art, TSP is used to remove impurities, but there is a chemical reaction that causes fluctuations in the effective ion concentration, which affects production efficiency.
A glass chemically strengthened salt bath additive is provided, which consists of SiO2, Na2O, Al2O3, K2O and rare earth oxides. Through ion exchange and adsorption, the effective ion concentration in the molten salt bath is maintained for a long time.
This additive can continuously and efficiently adsorb impurity ions, stabilize the effective ion concentration during the chemical strengthening of glass, extend the service life of the salt bath, reduce production costs, and improve production efficiency.
Smart Images

Figure CN119797780A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to a glass chemical strengthening salt bath additive and a preparation method and a recycling method thereof. Background Art
[0002] With the advancement of electronic information and glass processing technology, the application of ultra-thin glass has become more extensive. In order to cope with the problem of strength reduction caused by the reduction in thickness of ordinary glass, which is difficult to meet the challenges of the development of touch technology for electronic display screens, chemical strengthening has become one of the most commonly used means to improve the mechanical properties of glass. This process is usually carried out by immersing the glass substrate in a high-temperature molten salt bath. The basic principle is to strengthen the glass surface through ion exchange reaction. Specifically, small-radius alkali metal cations (such as lithium ions and sodium ions) in the glass will be replaced by large-radius alkali metal cations (such as sodium ions and potassium ions) in the salt bath, thereby forming a compressive stress layer on the glass surface. This stress layer significantly enhances the mechanical strength and impact resistance of the glass, making ultra-thin glass widely used in consumer electronics, smart cars and other fields.
[0003] In the process of chemical strengthening of ultra-thin glass, the effective ion concentration (such as Na + , K + For example, when chemically strengthening LAS series glasses with high lithium content, the continuous ion exchange and the introduction of impurity ions from the external environment will increase the impurity ions in the molten salt bath, which will affect the strengthening stability and mechanical properties of the glass after strengthening. Replacing the molten salt in the salt bath requires stopping production for many days, which greatly reduces production efficiency.
[0004] At present, the commonly used method for removing impurity ions in the industry is to add TSP (phosphate, which is a composite powder with sodium phosphate as the main component) to the molten salt bath. The impurity removal method is as follows: using the phosphate PO4 in TSP 3- With excessive cations in the molten salt (such as Li + ) and precipitate to the bottom of the chemical strengthening furnace, becoming a sludge-like state. However, on the one hand, TSP needs to be added multiple times during continuous long-term production, and the increasing amount of precipitates will continue to roll from the bottom of the strengthening furnace to the surface of the strengthened glass, affecting the surface of the glass; on the other hand, each time TSP is added, it will undergo a violent chemical reaction with the molten salt, causing the effective ion concentration in the molten salt to change dramatically in a short period of time, affecting the performance stability of glass strengthening.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a glass chemical strengthening salt bath additive and a preparation method and a recycling method thereof, aiming to provide a salt bath additive that can maintain the effective ion concentration in the molten salt bath during the glass chemical strengthening process for a long time, thereby solving the problem of the increasing amount of impurity ions in the glass chemical strengthening process affecting the glass properties.
[0007] The technical solution of the present invention is as follows:
[0008] In a first aspect of the present invention, there is provided a glass chemical strengthening salt bath additive, wherein, in terms of mole percentage, the glass chemical strengthening salt bath additive comprises the following components:
[0009] SiO2 52% to 68%, Na2O 1% to 25%, Al2O3 3% to 8%, K2O 1% to 25% and rare earth oxides 0% to 0.5%;
[0010] And the components satisfy at least one of the following conditions a to d:
[0011] a. 15%≤(Na2O+K2O)≤45%;
[0012] b. 5%≤Al2O3 / (Na2O+K2O)≤25%;
[0013] c. 0.8≤K2O / Na2O≤4.5;
[0014] d. 5%≤Al2O3 / SiO2≤15%.
[0015] Optionally, the molar percentage of the rare earth oxide is 0.1% to 0.5%; the rare earth oxide includes at least one of CeO2, Y2O3, Er2O3 and La2O3.
[0016] Optionally, the pH value of the glass chemical strengthening salt bath additive is 7-9.
[0017] Optionally, 1 wt% to 10 wt% of a glass chemical strengthening salt bath additive is added to the glass chemical strengthening molten salt bath, and after reacting at 400 to 560° C. for 3 to 240 hours, the absorption rate of the glass chemical strengthening salt bath additive for lithium ions is ≥55%.
[0018] Optionally, the glass chemical strengthening salt bath additive is in the form of particles, threads, fragments or plates;
[0019] When the glass chemical strengthening salt bath additive is in the form of fragments or plates, the thickness of the glass chemical strengthening salt bath additive is 0.2-0.8 mm.
[0020] Optionally, when the thickness of the glass chemical strengthening salt bath additive is 0.3 to 0.5 mm, the average transmittance of the glass chemical strengthening salt bath additive for light in the wavelength range of 360 to 780 nm is greater than or equal to 80%, and when the glass chemical strengthening salt bath additive is added to the glass chemical strengthening molten salt bath and immersed for more than 72 hours, the average transmittance of the glass chemical strengthening salt bath additive for light in the wavelength range of 360 to 780 nm is less than or equal to 50%.
[0021] Optionally, the ion concentration in the glass chemical strengthening molten salt bath to which the glass chemical strengthening salt bath additive is applied satisfies the following conditions:
[0022] Na + ≥150000ppm; and / or, K + ≥15000ppm; and / or, Li + ≥0ppm.
[0023] A second aspect of the present invention provides a method for preparing the glass chemical strengthening salt bath additive as described above, which comprises the following steps:
[0024] S1. According to the components and proportions of the glass chemical strengthening salt bath additive, the raw materials of the glass chemical strengthening salt bath additive are mixed, heated to 900-1400° C. and melted for a preset time to obtain a molten body;
[0025] S2. After the molten body is subjected to a molding treatment, the glass chemical strengthening salt bath additive is obtained; or, after the molten body is subjected to a molding treatment and an annealing treatment, the glass chemical strengthening salt bath additive is obtained.
[0026] Optionally, the preset time is 3 to 10 hours;
[0027] The forming process includes water quenching, pouring, drawing or rolling.
[0028] A third aspect of the present invention provides a method for recycling a glass chemical strengthening salt bath additive, which comprises the following steps:
[0029] The glass chemical strengthening salt bath additive of the present invention is added to a glass chemical strengthening molten salt bath, and after using the glass for chemical strengthening, the glass is recycled to obtain a recycled product;
[0030] The recycled materials are used as raw materials for producing lithium batteries and / or glass.
[0031] Beneficial effects: The glass chemical strengthening salt bath additive provided by the present invention does not contain phosphate salts. When added to the glass chemical strengthening molten salt bath, it can continuously and efficiently adsorb the impurity ions in the glass chemical strengthening molten salt bath, and can maintain the effective ion concentration in the molten salt bath used for glass chemical strengthening for a long time, efficiently and stably, thereby extending the service life of the molten salt bath, reducing production costs, and improving production efficiency. And because the composition of the glass chemical strengthening salt bath additive is basically the same as that of the ultra-thin glass, no harmful ions will be released in the salt bath. The glass chemical strengthening salt bath additive provided by the present invention can be recycled after use and used as raw materials for lithium batteries or the glass industry, which is recycled and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A morphology of the granular glass chemical strengthening salt bath additive in Example 1 before chemical strengthening.
[0033] Figure 2 The morphology of the granular glass chemical strengthening salt bath additive in Example 1 after chemical strengthening.
[0034] Figure 3 A morphology of the plate-shaped glass chemical strengthening salt bath additive in Example 3 before chemical strengthening.
[0035] Figure 4 The morphology of the plate-shaped glass chemical strengthening salt bath additive in Example 3 after chemical strengthening. DETAILED DESCRIPTION
[0036] The present invention provides a glass chemical strengthening salt bath additive and a preparation method and a recycling method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0038] An embodiment of the present invention provides a glass chemical strengthening salt bath additive, wherein, in terms of mole percentage, the glass chemical strengthening salt bath additive includes the following components:
[0039] SiO2 52% to 68%, Na2O 1% to 25%, Al2O3 3% to 8%, K2O 1% to 25% and rare earth oxides 0% to 0.5%;
[0040] And the components satisfy at least one of the following conditions a to d:
[0041] a. 15%≤(Na2O+K2O)≤45%;
[0042] b. 5%≤Al2O3 / (Na2O+K2O)≤25%;
[0043] c. 0.8≤K2O / Na2O≤4.5;
[0044] d. 5%≤Al2O3 / SiO2≤15%.
[0045] Among them, SiO2 and Al2O3 are network formers, and play the main skeleton role in the glass chemical strengthening salt bath additive. If the SiO2 content is too high, the network structure of the additive will be too dense, which is not conducive to ion exchange with lithium ions in the salt bath. Therefore, the molar content of SiO2 is 52% to 68%. For example, it can be 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68% or any value in the numerical range composed of any two of the above values as endpoints. Al2O3 can form a larger structure [AlO4], replacing the [SiO4] silicon-oxygen tetrahedron in the glass phase, which is convenient for ion exchange with lithium ions in the salt bath. Al2O3 can form [AlO4] to provide a larger space for ion exchange. Taking all factors into consideration, the molar content of Al2O3 is 3% to 8%, for example, it can be 3%, 4%, 5%, 6%, 7%, 8% or any value in a numerical range consisting of any two of the above values as endpoints.
[0046] Na2O belongs to the network exosome, and in the additive of the present invention, it plays the role of ion exchange with lithium ion impurities in the salt bath and adsorbing lithium ion impurities, and is an essential component of the additive. The higher the content of Na2O, the more conducive it is to increase the amount of lithium ions adsorbed by the unit mass of the salt bath additive. However, if the content of Na2O is too high, the additive will be corroded in the salt bath, silicon and the like will enter the salt bath or form suspended particles, which will lead to surface contamination and damage of the glass after chemical strengthening. Therefore, the molar content of Na2O is 1% to 25%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in the numerical range composed of any two of the above values as endpoints.
[0047] K2O is beneficial for absorbing lithium ion impurities in the potassium nitrate salt bath. Due to the large difference in radius between lithium ions and potassium ions, ion exchange between lithium and potassium is not easy to carry out. In the ion exchange process, the salt bath of lithium-containing glass generally adopts a two-step salt bath, that is, the first step is lithium-sodium exchange and the second step is sodium-potassium exchange. An appropriate amount of K element can improve the ion exchange efficiency. Therefore, the content of K2O is 1% to 25%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value in the numerical range composed of any two of the above values as endpoints.
[0048] The rare earth element oxide can be at least one of CeO2, Y2O3, Er2O3 and La2O3. Adding rare earth element oxide is beneficial to stabilizing the structure of the additive. Lanthanide elements have a high coordination number and a strong field, which makes the additive structure more compact and maintains its stability in the high-temperature molten salt bath, achieving long-term adsorption and extending the service life of the salt bath. Therefore, the molar percentage of rare earth element oxide is 0% to 0.5%, for example, it can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any value in the numerical range composed of any two of the above values as endpoints.
[0049] The glass chemical strengthening salt bath additive provided by the present invention does not contain phosphate salts. When added to the glass chemical strengthening molten salt bath, it can continuously and efficiently adsorb the impurity ions in the glass chemical strengthening molten salt bath that affect the stability of glass strengthening, and can maintain the effective ion concentration in the molten salt bath used for glass chemical strengthening for a long time, efficiently and stably, thereby extending the service life of the molten salt bath, reducing production costs, and improving production efficiency. And since the composition of the glass chemical strengthening salt bath additive is basically the same as that of the ultra-thin glass, no harmful ions will be released in the salt bath. The glass chemical strengthening salt bath additive provided by the present invention can be recycled after use and used as raw materials for lithium batteries or the glass industry, and recycled, which is green and environmentally friendly. The glass chemical strengthening salt bath additive provided by the present invention is an environmentally friendly additive with the characteristics of long-lasting, economical, highly applicable, environmentally friendly and pollution-free.
[0050] In the present invention, the glass chemical strengthening salt bath additive is applicable to a glass chemical strengthening molten salt bath that meets the following ion concentration conditions:
[0051] Na + ≥150000ppm; and / or, K + ≥15000ppm; and / or, Li + ≥0ppm.
[0052] In some embodiments, the glass chemical strengthening salt bath additive is in the form of particles, threads, fragments or sheets;
[0053] When the glass chemical strengthening salt bath additive is in the form of fragments or plates, the thickness of the glass chemical strengthening salt bath additive is 0.2 to 0.8 mm, for example, it can be 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm or any value in a numerical range consisting of any two of the above values as endpoints.
[0054] In some embodiments, when the glass chemical strengthening salt bath additive is in the form of fragments or plates, and the thickness of the glass chemical strengthening salt bath additive is 0.3 to 0.5 mm, the average transmittance of the glass chemical strengthening salt bath additive for light in the wavelength range of 360 to 780 nm is greater than or equal to 80%, and when the glass chemical strengthening salt bath additive is added to the glass chemical strengthening molten salt bath and immersed for more than 72 hours, the average transmittance of the glass chemical strengthening salt bath additive for light in the wavelength range of 360 to 780 nm is less than or equal to 50%.
[0055] In some embodiments, the pH value of the glass chemical strengthening salt bath additive is 7 to 9. The pH value of the glass chemical strengthening salt bath additive provided by the present invention is 7 to 9, showing weak alkalinity, which can ensure the stability of the pH value of the molten salt during the glass chemical strengthening process and will not cause adverse effects on the surface of the strengthened glass.
[0056] In some embodiments, 1 wt% to 10 wt% of a glass chemical strengthening salt bath additive is added to a glass chemical strengthening molten salt bath, i.e., 1% to 10% (e.g., 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.) of the glass chemical strengthening salt bath additive by mass is added to the glass chemical strengthening molten salt bath, and after reacting at 400 to 560° C. for 3 to 240 hours, the absorption rate of the glass chemical strengthening salt bath additive for lithium ions is ≥55%.
[0057] In some embodiments, the composition of the glass chemical strengthening molten salt bath may be 100 wt % sodium nitrate, or 70 wt % sodium nitrate + 30 wt % potassium nitrate, but is not limited thereto.
[0058] The embodiment of the present invention further provides a method for preparing the glass chemical strengthening salt bath additive as described above, wherein the method comprises the following steps:
[0059] S1. According to the components and proportions of the glass chemical strengthening salt bath additive, the raw materials of the glass chemical strengthening salt bath additive are mixed, heated to 900-1400° C. (for example, 900° C., 1000° C., 1100° C., 1200° C., 1300° C. or 1400° C.), and melted for a preset time to obtain a melt;
[0060] S2. After the molten body is subjected to a molding treatment, the glass chemical strengthening salt bath additive is obtained; or, after the molten body is subjected to a molding treatment and an annealing treatment, the glass chemical strengthening salt bath additive is obtained.
[0061] In step S1, in some embodiments, the preset time is 3 to 10 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.
[0062] In step S2, in some embodiments, the forming process includes water quenching, casting, drawing or rolling, etc., but is not limited thereto.
[0063] The embodiment of the present invention further provides a method for recycling a glass chemical strengthening salt bath additive, which comprises the following steps:
[0064] The glass chemical strengthening salt bath additive of the present invention is added to a glass chemical strengthening molten salt bath, and after using the glass for chemical strengthening, the glass is recycled to obtain a recycled product;
[0065] The recycled materials are used as raw materials for producing lithium batteries and / or glass.
[0066] The present invention will be further described below by means of specific examples.
[0067] The test methods involved in the following embodiments are as follows:
[0068] Lithium ion concentration test:
[0069] The concentration of lithium ions in the salt bath is tested by ICP (inductively coupled plasma). Specifically, an appropriate amount of molten salt bath with a lithium ion concentration to be measured is taken out from the strengthening furnace. After the molten salt bath is cooled, 0.25 g of the cooled solid material is accurately weighed into a 100 mL glass beaker, dissolved and shaken, and then diluted to a certain multiple. The concentration of lithium ions in the salt bath is tested by ICP and the corresponding standard curve.
[0070] Impurity ion absorption rate test method (taking lithium ion as an example):
[0071] The concentration of lithium ions in the molten salt bath after chemical strengthening without using the glass chemical strengthening salt bath additive is recorded as C1. 1wt% to 10wt% of the glass chemical strengthening salt bath additive is added to the molten salt bath, and the glass is chemically strengthened at 400 to 560°C and n (3h≤n≤240h) hours. At this time, the concentration of lithium ions in the molten salt bath after chemical strengthening using the glass chemical strengthening salt bath additive is recorded as C2. After each batch of glass is strengthened for 10 hours, it is taken out and replaced with another batch for continuous testing. After each batch of glass is strengthened, the concentration of lithium ions in the molten salt bath is tested by ICP (inductively coupled plasma).
[0072] Lithium ion absorption rate of glass chemical strengthening salt bath additive = (C1-C2) / C1×100%.
[0073] Transmittance test:
[0074] The light transmittance (i.e., visible light transmittance) of the plate-shaped additive in the wavelength range of 380nm to 780nm was tested using a PerkinElmer Lambda UV-visible spectrophotometer. Specifically, when using the additive, 2 to 4 plates of glass chemical strengthening salt bath additives were added during the strengthening process to perform a strengthening experiment for the transmittance test.
[0075] In the following examples and comparative examples, the components (molar percentage content) of the glass chemical strengthening salt bath additive, some process parameters and some test results are shown in Table 1.
[0076] Table 1. Components of the glass chemical strengthening salt bath additives in each embodiment, some process parameters and some test results
[0077]
[0078] Example 1
[0079] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0080] According to the components and proportions of the glass chemical strengthening salt bath additive in Example 1 in Table 1, the raw materials were mixed, heated to 1380° C. and melted for 3 hours to obtain a melt;
[0081] The melt is water quenched to obtain a granular glass chemical strengthening salt bath additive.
[0082] Example 2
[0083] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0084] According to the components and proportions of the glass chemical strengthening salt bath additives in Example 2 in Table 1, the raw materials were mixed, heated to 1400° C. and melted for 4 hours to obtain a melt;
[0085] The melt is water quenched to obtain a granular glass chemical strengthening salt bath additive.
[0086] Example 3
[0087] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0088] According to the components and proportions of the glass chemical strengthening salt bath additives in Example 3 in Table 1, the raw materials were mixed, heated to 1360° C. and melted for 6 hours to obtain a melt;
[0089] The molten body was cast, annealed at 400° C. for 6 hours, and then cut, grinded and polished to obtain a glass chemical strengthening salt bath additive in the form of a plate with a thickness of 0.4 mm.
[0090] Example 4
[0091] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0092] According to the components and proportions of the glass chemical strengthening salt bath additive in Example 4 in Table 1, the raw materials were mixed, heated to 1370° C. and melted for 5 hours to obtain a melt;
[0093] The melt is water quenched to obtain a granular glass chemical strengthening salt bath additive.
[0094] Example 5
[0095] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0096] According to the components and proportions of the glass chemical strengthening salt bath additive in Example 5 in Table 1, the raw materials were mixed, heated to 1360° C. and melted for 6 hours to obtain a melt;
[0097] The melt is water quenched to obtain a granular glass chemical strengthening salt bath additive.
[0098] Example 6
[0099] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0100] According to the components and proportions of the glass chemical strengthening salt bath additive in Example 6 in Table 1, the raw materials were mixed, heated to 1400° C. and melted for 4 hours to obtain a melt;
[0101] The molten body was cast, annealed at 400° C. for 6 hours, and then cut, grinded and polished to obtain a glass chemical strengthening salt bath additive in the form of a plate with a thickness of 0.4 mm.
[0102] Comparative Example 1
[0103] This embodiment provides a method for preparing a glass chemical strengthening salt bath additive, comprising the following steps:
[0104] According to the components and proportions of the glass chemical strengthening salt bath additive in Comparative Example 1 in Table 1, the raw materials were mixed, heated to 1360° C. and melted for 4 hours to obtain a melt;
[0105] The melt is water quenched to obtain a granular glass chemical strengthening salt bath additive.
[0106] Comparative Example 2
[0107] That is the existing TSP phosphate.
[0108] Lithium ion absorption rate test:
[0109] The glass chemical strengthening molten salt bath consisted of 100 wt % sodium nitrate.
[0110] (1) KK6 glass (purchased from China Southern Glass Group Co., Ltd., with a size of 40mm×60mm×0.65mm) and glass chemical strengthening salt bath additives (the glass chemical strengthening salt bath additives in Examples 1 to 6 and Comparative Example 2, respectively, and the mass of the glass chemical strengthening salt bath additives is 5% of the mass of the glass chemical strengthening molten salt bath) are added to the above-mentioned glass chemical strengthening molten salt bath for chemical strengthening. At a temperature of 450°C, after reacting for 10h, 60h, 120h, 160h, and 240h, samples of the salt bath are taken to test the lithium ion concentration. After each 10h of strengthening, another batch of the same type of glass is replaced. Before each glass is added, the bath salt needs to be taken to test the lithium ion concentration by ICP. For example, after strengthening for 240h, the glass has been replaced 24 times. The test results of lithium ion absorption rate are shown in Table 2. At the same time, the morphology of the granular glass chemical strengthening salt bath additive in Example 1 before chemical strengthening is shown in Table 2. Figure 1 The morphology of the granular glass chemical strengthening salt bath additive in Example 1 after chemical strengthening is shown in FIG. Figure 2 The morphology of the plate-shaped glass chemical strengthening salt bath additive in Example 3 before chemical strengthening is shown in FIG. Figure 3 The morphology of the plate-shaped glass chemical strengthening salt bath additive in Example 3 after chemical strengthening is shown in FIG. Figure 4 shown.
[0111] (2) Glass (composition: 69.2 mol% SiO2, 4.22 mol% Al2O3, 0.95 mol% P2O5, 1.70 mol% ZrO2, 1.58 mol% Na2O, 20.73 mol% Li2O and 1.62 mol% B2O3, size: 40 mm×60 mm×0.65 mm) and glass chemical strengthening salt bath additives (respectively, the glass strengthening salts in Examples 1 to 6 and Comparative Example 1) were prepared. Chemical strengthening salt bath additives (the mass of glass chemical strengthening salt bath additives is 5% of the mass of glass chemical strengthening molten salt bath) are added to the above glass chemical strengthening molten salt bath for chemical strengthening. At a temperature of 450°C, after reacting for 10h, 20h, 30h, 40h, and 50h, samples are taken from the salt bath to test the lithium ion concentration. After each 10h of strengthening, another batch of the same type of glass is replaced. Before each glass is added, the bath salt needs to be taken to test the lithium ion concentration by ICP. For example, after strengthening for 50h, the glass has been replaced 5 times. The test results of lithium ion absorption rate are shown in Table 3.
[0112] According to the formulas in Examples 1-6 and Comparative Example 1, they were all prepared into plate-shaped glass chemical strengthening salt bath additives with a thickness of 0.4 mm, and added to a glass chemical strengthening molten salt bath and immersed at 450°C for 72 hours, and the transmittance of the glass chemical strengthening salt bath additives was tested. At the same time, the transmittance of the glass chemical strengthening salt bath additives before immersion was tested. The results are shown in Table 3.
[0113] Table 2 Performance results of glass chemical strengthening salt bath additives in Examples 1 to 6 and Comparative Example 2
[0114]
[0115] Table 3 Performance results of glass chemical strengthening salt bath additives in Examples 1 to 6 and Comparative Example 1
[0116]
[0117] From the above results, it can be seen that the glass chemical strengthening salt bath additive provided by the present invention can continuously and efficiently adsorb impurity ions in the glass chemical strengthening molten salt bath, and can maintain the effective ion concentration in the molten salt bath used for glass chemical strengthening efficiently and stably for a long time.
[0118] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A glass chemical strengthening salt bath additive, characterized in that: The glass chemical strengthening salt bath additive comprises the following components in terms of mole percentage: SiO2 52% to 68%, Na2O 1% to 25%, Al2O3 3% to 8%, K2O 1% to 25% and rare earth oxides 0% to 0.5%; And the components satisfy at least one of the following conditions a to d: a. 15%≤(Na2O+K2O)≤45%; b. 5%≤Al2O3 / (Na2O+K2O)≤25%; c. 0.8≤K2O / Na2O≤4.5; d. 5%≤Al2O3 / SiO2≤15%.
2. The glass chemical strengthening salt bath additive according to claim 1, characterized in that: The molar percentage of the rare earth oxide is 0.1% to 0.5%; the rare earth oxide includes at least one of CeO2, Y2O3, Er2O3 and La2O3.
3. The glass chemical strengthening salt bath additive according to claim 1, characterized in that: The pH value of the glass chemical strengthening salt bath additive is 7-9.
4. The glass chemical strengthening salt bath additive according to claim 1, characterized in that: 1wt% to 10wt% of a glass chemical strengthening salt bath additive is added to a glass chemical strengthening molten salt bath, and after reacting at 400 to 560°C for 3 to 240 hours, the absorption rate of the glass chemical strengthening salt bath additive for lithium ions is ≥55%.
5. The glass chemical strengthening salt bath additive according to claim 1, characterized in that: The glass chemical strengthening salt bath additive is in the form of particles, threads, fragments or plates; When the glass chemical strengthening salt bath additive is in the form of fragments or plates, the thickness of the glass chemical strengthening salt bath additive is 0.2-0.8 mm.
6. The glass chemical strengthening salt bath additive according to claim 5, characterized in that: When the thickness of the glass chemical strengthening salt bath additive is 0.3-0.5 mm, the average transmittance of the glass chemical strengthening salt bath additive for light in the wavelength range of 360-780 nm is greater than or equal to 80%, and when the glass chemical strengthening salt bath additive is added to the glass chemical strengthening molten salt bath and immersed for more than 72 hours, the average transmittance of the glass chemical strengthening salt bath additive for light in the wavelength range of 360-780 nm is less than or equal to 50%.
7. The glass chemical strengthening salt bath additive according to claim 1, characterized in that: The ion concentration in the glass chemical strengthening molten salt bath to which the glass chemical strengthening salt bath additive is applied satisfies the following conditions: Na + ≥150000ppm; and / or, K + ≥15000ppm; and / or, Li + ≥0ppm.
8. A method for preparing the glass chemical strengthening salt bath additive according to any one of claims 1 to 7, characterized in that: The steps include: S1. According to the components and proportions of the glass chemical strengthening salt bath additive, the raw materials of the glass chemical strengthening salt bath additive are mixed, heated to 900-1400° C. and melted for a preset time to obtain a molten body; S2. After the molten body is subjected to a molding treatment, the glass chemical strengthening salt bath additive is obtained; or, after the molten body is subjected to a molding treatment and an annealing treatment, the glass chemical strengthening salt bath additive is obtained.
9. The preparation method according to claim 8, characterized in that: The preset time is 3 to 10 hours; The forming process includes water quenching, pouring, drawing or rolling.
10. A method for recycling glass chemical strengthening salt bath additives, characterized in that: The steps include: Adding the glass chemical strengthening salt bath additive according to any one of claims 1 to 7 to a glass chemical strengthening molten salt bath, performing glass chemical strengthening, and then recovering the recovered product after using the glass chemically strengthened to obtain a recovered product; The recycled materials are used as raw materials for producing lithium batteries and / or glass.